2016
DOI: 10.2174/1389202917666160805153221
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gene Variants of Unknown Significance: Analysis Method and Risk Assessment of the VHL Mutation p.P81S (c.241C>T)

Abstract: Background: Evaluation of the pathogenicity of a gene variant of unknown significance (VUS) is crucial for molecular diagnosis and genetic counseling, but can be challenging. This is especially so in phenotypically variable diseases, such as von Hippel-Lindau disease (vHL). vHL is caused by germline mutations in the VHL gene, which predispose to the development of multiple tumors such as central nervous system hemangioblastomas and renal cell carcinoma (RCC).Objective: We propose a method for the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Overall, 136 peer-reviewed publications based on registry data were identified. Of these, basic science was most commonly represented (80 papers [ 15‐94 ]) followed by clinical outcome (30 papers [ 95‐124 ]), quality and improvement (7 papers [ 125‐131 ]), treatment (6 papers [ 132‐137 ]), epidemiology (4 papers [ 98 , 138‐140 ]), patient-reported outcome (PRO) measure (1 paper [ 141 ]), and other (3 papers [ 142‐144 ]). Additionally, there were 5 registry-issued clinical practice guidelines [ 145‐149 ] published in collaboration with other institutions and specialty societies.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 136 peer-reviewed publications based on registry data were identified. Of these, basic science was most commonly represented (80 papers [ 15‐94 ]) followed by clinical outcome (30 papers [ 95‐124 ]), quality and improvement (7 papers [ 125‐131 ]), treatment (6 papers [ 132‐137 ]), epidemiology (4 papers [ 98 , 138‐140 ]), patient-reported outcome (PRO) measure (1 paper [ 141 ]), and other (3 papers [ 142‐144 ]). Additionally, there were 5 registry-issued clinical practice guidelines [ 145‐149 ] published in collaboration with other institutions and specialty societies.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant in the case when Variants of Unknown Significance (VUS) are identified in patients. These genetic variations for which we do not know the molecular and physiological consequences represent a significant dilemma in genetic diagnosis and genetic counseling ( Alosi et al, 2017 ). Indeed, according to the American College of Medical Genetics and Genomics (ACMG) guidelines, VUS should not be used in clinical decision-making ( Richards et al, 2015 ).…”
Section: Using Zebrafish To Predict Neurological Disease Susceptibili...mentioning
confidence: 99%
“…Among the 1230 mutations listed in the VHL database (http://umd.be/VHL) some mutants still remain biochemically uncharacterized [3]. Referred families diagnosed with P81S mutation linked to low penetrance Type 1 von Hippel-Lindau disease and a mild phenotype [9] [10]. A previous study investigating defects Type 2C associated mutant protein demonstrated at the molecular level the deleterious role involvement of pVHL L188V , pVHL P81S/L188V , pVHL V84L.…”
Section: Accepted Manuscript / Final Versionmentioning
confidence: 99%